Estadios ninfales de los coreidos del valle de Tehuacan, Puebla, México (Hemiptera-Heteroptera). II. Especies asociadas a huizacheras (Acacia spp.) Y mezquiteras (Prosopis spp.): Mozena lunata, Pachylis hector, Savius jurgiosus y Thasus gigas - BRAILOVSKY, HARRY; ORTEGA LEÓN, GUILLERMINA; BARRERA, ERNESTO; MAYORGA, CRISTINA (Anales del Instituto de Biología serie Zoología, 2009)
A STUDY OF INMATURE STAGES OF MOZENA LUNATA( BURMEISTER), PACHYLIS HECTOR STAL, SAVIUS JURGIOSUS JURGIOSUS (STAL) AND THASUS GIGAS (BURMEISTER), IS OFFERED. THE EXTERNAL MORPHOLOGICAL CHARACTERS OF THE FIVE INSTARS, AS WELL AS THE EGGS OF MOST OF THE SPECIES ARE DESCRIBED AND FIGURED. SOME BIOLOGICAL AND ETHOLOGICAL ASPPECTS ARE ASSOCIATED WITH SWEET ACACIA (ACACIA SPP. ) AND MEZQUITE ( PROSOPIS SPP.) IN THE VALLEY OF TEHUACÁN IN THE STATE OF PUEBLA , MEXICO.